BISNIS DROPSHIPPING KOSMETIKA PADA SHOPEE MENURUT FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA NO: 145/DSN-MUI/XII/2021 TENTANG DROPSHIP BERDASARKAN PRINSIP SYARIAH - Qurrotul Uyun; Rusdi Sulaiman; Anggita Anggriana (Al-Aqad, 2024)
This study aims to determine the mechanism of dropshipping cosmetics business in shopee according to the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 145/DSN-MUI/XII/2021 concerning Dropshipping Based on Sharia Principles: 145/DSN-MUI/XII/2021 concerning Dropship Based on Sharia Principles. This research uses qualitative methods with empirical normative research. Data sources were obtained from the results of drop shipper interviews on the shoppe application. While secondary data is obtained through primary legal material, namely the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 145/DSN-MUI/XII/2021 on Dropship Based on Sharia Principles: 145/DSN-MUI/XII/2021 concerning Dropship Based on Sharia Principles and other materials such as books, journals, laws, and articles related to the research. Data collection techniques through observation, interviews, and documentation. The results showed 1). In starting a dropshipping business on the Shopee application, the first step that must be taken by a Shopee drop shipper is to create a Shopee account and store account and find the right cosmetics supplier. When there is an order from the buyer, the drop shipper orders it to the supplier, using the buyer's address as the shipping destination and activating the send feature as a drop shipper. Sales funds will be received by the supplier and dropshipper when the buyer or dropshipper clicks the order is complete or the warranty period in the shopee application has expired. Buyers can also return goods or funds for certain reasons before the warranty period ends. 2). The dropshipping mechanism in the shopee application is in accordance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 145/DSN-MUI/XII: 145/DSN-MUI/XII/2021 Regarding Dropship Based on Sharia Principles.